Pengembangan Strategi Bisnis pada UKM Pabrik Tahu melalui Pendekatan Business Model Canvas (Studi Kasus: UD Sumber Makmur) - Ikhsan Ainur Rohman; Roro Ananda Setyawardhani; Tsabit Wardana; Retno Indriartiningtas (Metris: Jurnal Sains dan Teknologi, 2026)
UD Sumber Makmur, a small-scale tofu manufacturer in Bangkalan, currently faces significant business stagnation due to limited market reach. This study aims to formulate comprehensive business development strategies to solve this distribution limitation and address stiff competition. The research employs a qualitative descriptive method, with data collected directly through in-depth interviews and observations at the production site. The Business Model Canvas (BMC) is utilized to map the current business architecture. The resolution strategy involves integrating these tools to design a new business model that specifically targets market expansion. The results recommend actionable strategies, including expanding distribution channels to all areas Bangkalan, adopting digital marketing to reach broader consumer segments, diversifying into processed tofu products, and modernizing machinery to support increased demand. These measures are expected to resolve the limited market reach issue and ensure future business sustainability.